Etika Terhadap Lingkungan: Suatu Kajian Filsafati dalam Konteks Epidemiologi Penyakit - Agus Kharmayana Rubaya (Sanitasi: Jurnal Kesehatan Lingkungan, 2013)
Models which were developed by epidemiologists about the theory of diseases, always refer tothe importance of the interaction among human as disease host, environment and disease agents. Based on the complexity of the relationship between human and their surrounding environment, in epidemiological point of view, how the environment is treated and perceived by human is necessary to be investigated. This paper tries to present a study about some ethics systems which are widely known, and at the same time also tries to discuss some highly correlatedaspects, in the context of disease epidemiology. Ethics system of anthropocentrism or shallowenvironmental ethics which considers human as the centrum and the only possessor of the entire universe, and therefore they are permitted to do anything for their satisfaction and needs,give justification to the exploitation of the earth which are actually, sooner or later, the unneededimpacts, will affect the human being. The anthropocentrisme ethics is refused by biocentrismethics or intermediate environmental ethics and ecocentrism ethics or deep environmental ethicswhich were born from the revitalization spirit of local wisdoms from traditional communities inmany countries in encountering the hegemony of western cultures. In responding to the insertionof external culture and technology, some issues must be prudently seen, such as: instead ofgaining advantages, inappropriate application of technology may causing disadvantages; and thejoining culture which is attached to the technology may change the existing life-style, consumption pattern and the insight of the society; so that, it is crucial for the government to be involvedby endorsing healthy public policy. To conclude, ethics system which has to be supported is theone that appreciates every elements in ecosystem as important as the others; and it is also important to forming environmentally caring generation through early age education.